Aboriginal Research: Berry Picking and Hunting in the 21st Century - Absolon, Kathy; Willett, Cam (First Peoples Child & Family Review, 2004)
In this article issues around research methodology specific to Aboriginal people will be discussed. A brief historical analysis lays a foundation for the need for unique research methodologies as it pertains to Aboriginal people both as researched and researcher. Contemporary critiques by Aboriginal writers and communities will be presented in relation to the limitations and effects of Euro-western research methods. Finally, the authors will discuss issues, possibilities and responsibilities around conducting research as Aboriginal researchers.